Universalitas Ham dan Sakralitas Syariah (Respon Muslim Konservatif, Liberal dan Progresif Atas Gagasan Ham Internasional) - nurrochman nurrochman (LP2M IAIN Palangka Raya, 2017)
Universal human rights raises much debate among muslims. There are at least three opinions on international human rights. First, a conservative groups that rejects human rights because it comes from Western civilization and is considered contrary to shariah. Second, the liberal groups who accepted the idea of human rights and argue that human rights and Islam are compatible. Third, progressive groups who accept human rights as a concept that compatible with Islam, but the practice must be criticized. In the modern era, muslim ara faced with many challenges. Islamic law is required to be able to answer the challenges of the times. The idea of reformation of Islamic law has actually been appearing since the era of classical jurisprudence. But unfortunately received less attention. This paper is one of the efforts to recall that the ideal of Islamic law reformation is very important, especially concerning the issues of human rights.